Trade, product variety and welfare: a quantitative assessment for the transition economies in Central and Eastern Europe - Michael Funke; Ralf Ruhwedel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
We calculate welfare gains of trade liberalization in the Central and East European transition economies, following the approach of Romer (1994), who emphasized that proper modeling of the impact of trade restrictions on the number of available product varieties is crucial to quantifying the welfare impact of trade liberalization. The empirical work relies on direct measures of product variety calculated from 5-digit trade data.Although the issue is far from settled, the emerging conclusion is that freer trade has boosted welfare. Trade Liberalization, Product Variety, Welfare, Transition Economies D60, F14, F15
URN:NBN:fi:bof-201408072211
Keywords: D60; F14; F15; 330